The journal of conflict resolution
Journal of Conflict Resolution (JCR), peer-reviewed and published eight times a year, for more than fifty years has provided scholars and researchers with the latest studies and theories on the causes of and solutions to the full range of human conflict. JCR focuses on conflict between and within states, but also explores a variety of inter-group and interpersonal conflicts that may help in understanding problems of war and peace.